2008
DOI: 10.1016/j.physbeh.2007.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions in energy balance: Does nature overcome nurture?

Abstract: Fat accumulation, in general, is the result of a breakdown in the homeostatic regulation of energy balance. Although, the specific factors influencing the disruption of energy balance and why these factors affect individuals differently are not completely understood, numerous studies have identified multiple contributors. Environmental components influence food acquisition, eating, and lifestyle habits. However, the variability in obesity-related outcomes observed among individuals placed in similar controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The number of overweight and obese people is rising substantially as a result of high-calorie diets and increasingly sedentary lifestyles that have become common in modern society [1]. Obesity, in particular 'android obesity', characterized by abdominal-visceral fat accumulation [2], is associated with increased insulin resistance [3] and is a major risk factor for the development of type 2 diabetes (T2D) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The number of overweight and obese people is rising substantially as a result of high-calorie diets and increasingly sedentary lifestyles that have become common in modern society [1]. Obesity, in particular 'android obesity', characterized by abdominal-visceral fat accumulation [2], is associated with increased insulin resistance [3] and is a major risk factor for the development of type 2 diabetes (T2D) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, at least 155 million children worldwide were overweight or obese, according to the International Obesity Task Force 3. Perhaps the most remarkable public health concern is the increase in overweight and obese children and adolescents 4. Obesity leads to serious consequences: type‐2 diabetes, hypertension, fatty liver disease, coronary heart disease, stroke, and cancer 5…”
Section: Introductionmentioning
confidence: 99%
“…The reason for obesity is a dysregulated energy balance, energy intake and energy expenditure being unequal. In understanding the role of genes and environment it was found that the major impact was the environment (Fernandez et al, 2008;Papas et al, 2007). A relevant environmental factor is the ready availability of palatable energy-dense food containing fat and/or sucrose (Blundell et al, 2005;Lindqvist et al, 2005).…”
Section: Introductionmentioning
confidence: 99%